The devil's tabernacle - Ossa-Richardson, Anthony (Princeton Univ. Press, 2013)
The Devil's Tabernacle is the first book to examine in depth the intellectual and cultural impact of the oracles of pagan antiquity on modern European thought. Anthony Ossa-Richardson shows how the study of the oracles influenced, and was influenced by, some of the most significant developments in early modernity, such as the Christian humanist recovery of ancient religion, confessional polemics, Deist and libertine challenges to religion, antiquarianism and early archaeology, Romantic historiography, and spiritualism. Ossa-Richardson examines the different views of the oracles since the Renaissance–that they were the work of the devil, or natural causes, or the fraud of priests, or finally an organic element of ancient Greek society. The range of discussion on the subject, as he demonstrates, is considerably more complex than has been realized before: hundreds of scholars, theologians, and critics commented on the oracles, drawing on a huge variety of intellectual contexts to frame their beliefs. In a central chapter, Ossa-Richardson interrogates the landmark dispute on the oracles between Bernard de Fontenelle and Jean-Francois Baltus, challenging Whiggish assumptions about the mechanics of debate on the cusp of the Enlightenment. With erudition and an eye for detail, he argues that, on both sides of the controversy, to speak of the ancient oracles in early modernity was to speak of one's own historical identity as a Christian.
9780691157115
Keywords: Hochschulschrift; Oracles; Europe